2018
DOI: 10.1063/1.5007726
|View full text |Cite
|
Sign up to set email alerts
|

Iron-rich (Fe1-x-yNixCoy)88Zr7B4Cu1 nanocrystalline magnetic materials for high temperature applications with minimal magnetostriction

Abstract: As inductor technology advances, greater efficiency and smaller components demand new core materials. With recent developments of nanocrystalline magnetic materials, soft magnetic properties of these cores can be greatly improved. FeCo-based nanocrystalline magnetic alloys have resulted in good soft magnetic properties and high Curie temperatures; however, magnetoelastic anisotropies persist as a main source of losses. This investigation focuses on the design of a new Fe-based (Fe,Ni,Co)88Zr7B4Cu1 alloy with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…It should be note that the data shown in Figure and are consistent with the XRD results of Knipling et al This is confirmed by the XRD results that all peaks are assigned to the cubic phase of α‐FeCo (Figure and ). These results indicate that the ribbon produced in this study has the same stoichiometry, as reported in the study by Knipling et al In particular, in a study by Martone et al, they investigated the effects of Ni and Co contents on the magnetic properties in Fe 77 Ni 5.5 Co 5.5 Zr 7 B 4 Cu 1 . By systematically varying Ni from 5.5 to 14.667 and Co from 5.5 to 7.333 (whereas Fe, Zr, B, and Cu contents remain the same), they found that the magnetic properties such as H c and M s are not significantly changed.…”
Section: Resultssupporting
confidence: 80%
“…It should be note that the data shown in Figure and are consistent with the XRD results of Knipling et al This is confirmed by the XRD results that all peaks are assigned to the cubic phase of α‐FeCo (Figure and ). These results indicate that the ribbon produced in this study has the same stoichiometry, as reported in the study by Knipling et al In particular, in a study by Martone et al, they investigated the effects of Ni and Co contents on the magnetic properties in Fe 77 Ni 5.5 Co 5.5 Zr 7 B 4 Cu 1 . By systematically varying Ni from 5.5 to 14.667 and Co from 5.5 to 7.333 (whereas Fe, Zr, B, and Cu contents remain the same), they found that the magnetic properties such as H c and M s are not significantly changed.…”
Section: Resultssupporting
confidence: 80%